Relationship of Religiosity and Personality Dimensions with Rehabilitation Pracririoner Students Satisfaction with their Clinical Experiences - Yaser Rezapour-Mirsaleh; Kianoush A'bdi; Masoud Karimlou; Shahnaz Reyhani-Kivi (Journal of Rehabilitation, 2010)
Obgective: The purpose of present study was to investigate the relationship of religiosity and personality dimensions with satisfaction of rehabilitation practitioner students about their clinical experiences as a therapist.